The executioners three - Dennard, Susan (A Tor Teen Book, published by Tom Doherty Associates/Tor Publishing Group, 2025)
"Freddie Gellar didn't mean to get half the rival high school arrested. She'd simply heard shrieks coming from the woods, so she'd called the cops like any good human would do. How was she supposed to know it was just kids partying? Except the next day, a body is found. And while the local sheriff might call it suicide, Freddie's instincts tell her otherwise. So, like the aspiring sleuth (and true X-Files aficionado) she is, Freddie sets out to prove there's a murderer at large. But her investigation is quickly disrupted by the rivalry between her school and the school of the partying teens she got arrested. For over twenty years, the two student bodies have had an ongoing prank war, and Freddie's failed attempt at Good Samaritanism has upped the ante. Worse, the clever -- and gorgeous -- leader of the rival prank squad has set his sights on Freddie. As more pranks unfurl, more bodies also start piling up in the forest. But it's the supernatural warning signs around town, each plucked straight from an old forgotten poem called "The Executioners Three," that worry Freddie the most. She knows the poem and its blood curse can't be real, but she's quickly running out of time to prove it. Because the murderer -- or executioners? -- knows she's onto them now, and their next target just might be Freddie." --